EFFORTS TO IMPROVE CLEAN CULTURE IN CITIZENS OF SMP NEGERI 1 SINDANGRESMI THROUGH THE WASTE BRUSH MOVEMENT - Ato Adiarto (Cakrawala Pedagogik, 2023)
The problem discussed in this study is about the efforts made by the school principal through policies related to environmental hygiene, especially the waste problem through the declaration of a real action in fighting or cleaning up waste from the school environment. This movement aims to improve the clean culture of SMP Negeri 1 Sindangresmi Pandeglang. The procedure for this research is School Action Research (PTS) with a cycle of 2 cycles, with stages; Planning, implementation, observation and evaluation as well as reflection activities and preparation of reports. From the results of data collection and analysis, it can be stated that the percentage of clean culture awareness in schools before the action was recorded at 46.67% of students in the sufficient category, 7.57% was classified as good and 17% was classified as low. After the implementation of the declaration of the Garbage Brush Action Movement, there was an increase of 23.5% which was classified as very good, 73.3% was classified as good and 19.62% was classified as sufficient. The expected benefits are: 1. Theoretical benefits, namely adding to the scientific treasury regarding the formation of a cleaning team and improving clean culture. As input for other researchers who wish to examine the issue of clean culture in schools. 2. Practical Benefits, which can be used as a solution to improve a clean culture in the school environment. Become a reference material for school principals in improving a clean culture in schools. The results of this study are that there is an increase in clean culture among the residents of SMP Negeri 1 Sindangresmi Pandeglang, after the declaration of the Garbage Brush Action Movement it was recorded at 80.00% both for teachers and TU staff and for students, and it is true that with a clean culture it turns out that schools more clean, beautiful and healthy. The conclusion from the results of this study is that the formation of a cleaning team can improve a clean culture in the residents of SMP Negeri 1 Sindangresmi Pandeglang.